Forward genetic studies reveal LsAPRR2 as a key gene in regulating the green color of pericarp in bottle gourd (Lagenaria siceraria) - Huo, Yulai; Zhang, Gui; Yu, Wenjin; Liu, Zhengguo; Shen, Mujie; Zhao, Rongchong; Hu, Shengping; Zheng, Xuyang; Wang, Peng; Yang, Yanjuan (Frontiers in Plant Science, 2023)
Abstract The fruit peel color is an important factor that affects its quality. However, genes involved in regulating pericarp color in bottle gourd (Lagenaria siceraria) have not been explored to date. Genetic analysis of color traits in bottle gourd peel through a genetic population of six generations demonstrated that the green color of peels is inherited as a single gene dominant trait. Combined phenotype-genotype analysis of recombinant plants using BSA-seq mapped the candidate gene to a 22.645 Kb interval at the head end of chromosome 1. We observed that the final interval contained only one gene, LsAPRR2 (HG_GLEAN_10010973). Sequence and spatiotemporal expression analyses of LsAPRR2 unraveled two nonsynonymous mutations (A→G) and (G→C) in the parental CDS sequences. Further, LsAPRR2 expression was higher in all green-skinned bottle gourds (H16) at various stages of fruit development than in white-skinned bottle gourds (H06). Cloning and sequence comparison of the two parental LsAPRR2 promoter regions indicated 11 bases insertion and 8 SNPs mutations in the region -991～-1033, upstream of the start codon in white bottle gourd. Proof of GUS reporting system, Genetic variation in this fragment significantly reduced the expression of LsAPRR2 in the pericarp of white bottle gourd. In addition, we developed a tightly linked (accuracy 93.88%) InDel marker for the promoter variant segment. Overall, the current study provides a theoretical basis for comprehensive elucidation of the regulatory mechanisms underlying the determination of bottle gourd pericarp color. This would further help in the directed molecular design breeding of bottle gourd pericarp.